Survey on person re‐identification based on deep learning. Issue 4 (11th July 2018) - Wang, Kejun; Wang, Haolin; Liu, Meichen; Xing, Xianglei; Han, Tian
Abstract : Person re‐identification (Re‐ID) is a fundamental subject in the field of the computer vision technologies. The traditional methods of person Re‐ID have difficulty in solving the problems of person illumination, occlusion and attitude change under complex background. Meanwhile, the introduction of deep learning opens a new way of person Re‐ID research and becomes a hot spot in this field. This study reviews the traditional methods of person Re‐ID, then the authors focus on the related papers about different person Re‐ID frameworks on the basis of deep learning, and discusses their advantages and disadvantages. Finally, they propose the direction of further research, especially the prospect of person Re‐ID methods based on deep learning.